2009
DOI: 10.1371/journal.pmed.1000087
|View full text |Cite
|
Sign up to set email alerts
|

Will the Public's Health Fall Victim to the Home Foreclosure Epidemic?

Abstract: Gary Bennett and colleagues discuss the ways in which the dramatic rise in home foreclosures, particularly in the US, may have health consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 89 publications
2
37
1
1
Order By: Relevance
“…Relationships have also been observed with increases in crime rates [27][28][29][30][31] and racial segregation [32,33]. Several studies have also focused on the negative effects that increases in the number of foreclosures have had on public health [34][35][36][37] and on how different groups of local residents perceive the quality of life in their respective neighborhoods [38].…”
Section: Introductionmentioning
confidence: 99%
“…Relationships have also been observed with increases in crime rates [27][28][29][30][31] and racial segregation [32,33]. Several studies have also focused on the negative effects that increases in the number of foreclosures have had on public health [34][35][36][37] and on how different groups of local residents perceive the quality of life in their respective neighborhoods [38].…”
Section: Introductionmentioning
confidence: 99%
“…8 It has been postulated that, for some individuals, the foreclosure process may contribute to poor health. 8,22 Financial strain in general has been linked to worse health 10,11,15,23 and job loss-itself a cause of foreclosure-is associated with increased rates of depressive symptoms. 24 In a study utilizing screening questions, people undergoing foreclosure have been found to have high rates of depression.…”
Section: Discussionmentioning
confidence: 99%
“…29 High blood pressure and diabetes are linked to the emotional stress of housing insecurity. 30 Rapid urbanization leads to deteriorating health among the least advantaged of our population. Some federal policies have had a ripple effect on the availability of affordable housing in our modern cities and the attendant health of urban dwellers.…”
Section: 25mentioning
confidence: 99%